Diagnostic Accuracy of Ultrasound in Morbidly Adherent Placenta Keeping Histopathology as Gold Standard - Abid Hussain Jamali, Anam Sherwani, Altaf Sheikh, Kashmala Farhat, Samreen Tariq, Iqra Mustafa, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Morbidly adherent placenta has three varieties, each with varying degrees of invasion according to histopathology. The placenta accreta, increta, and percreta are a few of these. Clinical manifestations can include haemorrhage that is potentially fatal. Therefore, it's critical to make an early and rapid diagnosis of this ailment. Objective: To determine the diagnostic accuracy of ultrasound in morbidly adherent placenta keeping histopathology as the gold standard. Study design: Cross-sectional study Place and Duration: Department of Radiology, Liaquat University of Medical and Health Sciences, Jamshoro from 28th August 2021 till 1st March 2022. Methodology: Women over 35 who were pregnant and had a history of caesarean sections, placenta previa, or multiple pregnancies were included. A 2 x 2 table was used to compute the sensitivity, specificity, positive predictive value (PPV), negative predictive values (NPV), and accuracy. Stratification was used to manage effect modifiers. Diagnostic accuracy after stratification was calculated. Results: The patients were 37.38± 1.19 years old on average. The patients' mean gestational age was 37.94± 1.07 years. A total of 72 (41.60%) people had previously undergone a C-section, whereas 101 (58.40%) did not. In terms of diagnosing a morbidly adherent placenta, ultrasound had a sensitivity, specificity, PPV, NPV and diagnostic accuracy of 82.09%, 76.92%, 92.44%, 55.56%, and 80.92%, respectively, when using histology as the gold standard. Conclusion: The diagnosis of a morbidly adherent placenta can be made with good diagnostic sensitivity, specificity, and accuracy using ultrasound. Keywords: Ultrasound; Histopathology; Sensitivity, Morbidly Adherent Placenta